3-Hydroxysalicylaldehyde benzoylhydrazone - Basirun, Wan Jefrey; Ng, S.W.; Ali, H.M.; Puvaneswary, S. (International Union of Crystallography, 2005)
The crystal structure of 3-hydroxysalicylaldehyde benzoylhydrazone was analyzed. The planar conformation of the salicylaldehyde-benzoyl-hydrazone class of Schiff bases originated from water molecules that stabilized the structures. 3-hydroxysalicylaldehyde benzoylhydrazone possessed a 3-hydroxy substituent that was capable of stabilization, but the compound did not contain water. Meanwhile, the amido H atom formed a short hydrogen bond with the amido O atom of an adjacent molecule to give rise to a linear chain running along the shortest axis of the orthorhombic unit cell.